Basic fibroblast growth factor-syndecan complex at cell surface or immobilized to matrix promotes cell growth. - Markku Salmivirta; Jyrki Heino; Markku Jalkanen (1992)
Promotion of cell growth and differentiation by growth factors during early development and organ formation are both temporally and spatially very precise. Syndecan is a well characterized integral membrane proteoglycan that binds several extracellular matrix components via its heparan sulfate chains and is therefore suggested to participate in cell regulation. Syndecan-like molecules, as low affinity receptors for heparin-binding growth factors, have been recently suggested to also regulate growth factor activity. Heparin/heparan sulfate interaction is required before, e.g. basic fibroblast growth factor (bFGF) can associate with its high affinity cell surface receptors and trigger signal transduction. In this paper we show that syndecan, but not free heparan sulfate chains, can simultaneously bind both bFGF and extracellular matrix molecules. Moreover, increased DNA synthesis of 3T3 cells was observed when the 3T3 cells were exposed to beads coated with the fibronectin-syndecan-bFGF complex, indicating that bFGF remains biologically active even when immobilized to matrix via the heparan sulfate chains of syndecan. Finally, when bFGF was bound to the surface of another cell type (epithelial), co-culture with 3T3 cells stimulated 3T3 cell growth. Therefore, we suggest that syndecan-like molecules may determine sites of growth factor action at cell-matrix and cell-cell interfaces.